Intra-cycle depolarization of ultraintense laser pulses focused by off-axis parabolic mirrors. (6th June 2018) - Labate, Luca; Vantaggiato, Gianluca; Gizzi, Leonida A.
Abstract : A study of the structure of the electric and magnetic fields of ultraintense laser pulses focused by an off-axis parabolic mirror is reported. At first, a theoretical model is laid out, whose final equations integration allows the space and time structure of the fields to be retrieved. The model is then employed to investigate the field patterns at different times within the optical cycle, for off-axis parabola parameters normally employed in the context of ultraintense laser–plasma interaction experiments. The results show that nontrivial, complex electromagnetic field patterns are observed at the time at which the electric and magnetic fields are supposed to vanish. The importance of this effect is then studied for different laser polarizations, $f$ numbers and off-axis angles.